2022
DOI: 10.1016/j.jcmg.2021.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Left Atrial Infiltration in Cardiac Transthyretin Amyloidosis

Abstract: Objectives The aim of this study was to characterize left atrial (LA) pathology in explanted hearts with transthyretin amyloid cardiomyopathy (ATTR-CM); LA mechanics using echocardiographic speckle-tracking in a large cohort of patients with ATTR-CM; and to study the association with mortality. Background The clinical significance of LA involvement in ATTR-CM is of great clinical interest. Methods Congo red staining and immunohistochemistry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 27 publications
3
73
0
3
Order By: Relevance
“…Additionally, there was significant impairment of the 3 phasic functional atrial components (atrial reservoir, conduit and contraction function); indeed 22% of patients in sinus rhythm with atrial electromechanical dissociation had absent atrial contraction. The extensive amyloid infiltration of the left atria on echocardiogram in this study was corroborated with histological analysis of explanted ATTR hearts (33).…”
Section: Echocardiographysupporting
confidence: 78%
See 2 more Smart Citations
“…Additionally, there was significant impairment of the 3 phasic functional atrial components (atrial reservoir, conduit and contraction function); indeed 22% of patients in sinus rhythm with atrial electromechanical dissociation had absent atrial contraction. The extensive amyloid infiltration of the left atria on echocardiogram in this study was corroborated with histological analysis of explanted ATTR hearts (33).…”
Section: Echocardiographysupporting
confidence: 78%
“…The severity of dysfunction measured by a range of echocardiographic parameters was also shown to differ substantially at the time of diagnosis between patients with three important ATTR-CM genotypes. Those with p.V142I-associated ATTR-CM had the worst echocardiographic parameters, followed by wtATTR-CM and finally p.T80Aassociated ATTR CM, entirely consistent with the prognosis of these three conditions (33).…”
Section: Echocardiographysupporting
confidence: 66%
See 1 more Smart Citation
“…Of interest, a recent study with a large cohort of ATTR cardiomyopathy found atrial electromechanical dissociation in the presence of sinus rhythm within a small proportion of patients. The prognosis for patients with atrial electromechanical dissociation was significantly worse than for patients found with effective booster function and was comparable with patients in atrial fibrillation 16 . In view of new medical therapies recently introduced to block specific stages of amyloidogenesis, there is an opportunity to further investigate LA phasic changes and how these coincide with medical management.…”
Section: Discussionmentioning
confidence: 77%
“…In our CA cohort we noted that LA booster function was significantly impaired and did not compensate for decreased reservoir function. Although, the loss of LA compliance in CA has been explained as obligatory in response to direct amyloid fibril deposits in atrial walls limiting atrial stretch 15 , 16 an apparent reduced booster strain may also be an integral parameter to consider. Of interest, a recent study with a large cohort of ATTR cardiomyopathy found atrial electromechanical dissociation in the presence of sinus rhythm within a small proportion of patients.…”
Section: Discussionmentioning
confidence: 99%